Perancangan Alat Simulasi Sistem Kendali Lampu Rumah Menggunakan Aplikasi Android - Muhammad Syahputra Novelan (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Smartphones with the Android operating system are increasingly available in the market at increasingly affordable prices. The Android operating system itself is an open source operating system that can be modified according to needs. In this research, the aim is to design and implement a home lighting control system that activates and deactivates via a smartphone using Bluetooth and makes Android a multifunctional cellular device, in addition to a communication device but also as a device that is communicated to control a hardware device. Based on the results of tests conducted, the system can work properly in accordance with the goals of the lamp control application program that is made to run on the Android operating system, and can activate and deactivate the lamp driver device. Data communication between the lamp driver device and the Android smartphone runs well, the range of the control application system can control the lamp driver device depending on the specifications of the Bluetooth device used both from the receiver and sender side Keywords : Smartphone, Android, Full Control System, Bluetooth